INFLUENCE OF THE TYPE OF STATE SYSTEM ON CONSTITUTIONAL LEGISLATION: SOME ISSUES OF THEORY AND PRACTICE (by the example of the Russian Federation and Kazakhstan Republic) - T. Z. Zhunuskanov (Russian Journal of Economics and Law)
Objective: to study the basic laws of the constitutional law functioning of Kazakhstan Republic and the Russian Federation and its subjects in the system of law and legislation as an institutional phenomenon; to study the impact of government form on the constitutional law of the state. Methods: general scientific dialectic approach to cognition (comparative-legal, theoretical, predictive, etc.) and other methods (integral, institutional, situational, systemic-functional, etc.) have been used in combination with the requirements of objectivity, comprehensiveness, historicism, specificity and consistency, generally accepted in the analysis of the state-legal phenomena. Results: on the basis of comparative legal analysis of the Kazakhstan Constitution, the Constitutions and charters of subjects of the Russian Federation, normative legal acts regulating the constitutional-legal relations and research of the views of scientists on this topic, the impact of government form on the constitutional law of a state was examine; a conclusion was made about the significance of the Constitution in shaping the constitutional law. Scientific novelty: for the first time, with the use of the public methods, the role of the Constitution and constitutional legislation of the countries in the development of the modern Russian-Kazakhstan legal discourse was investigated. The impact of government form on constitutional law was analyzed, the concept of constitutional law was proposed. Practical value: the main provisions and conclusions of the article can be used in scientific and pedagogical activity when addressing issues of the role of the Constitution and constitutional law in the development of the legal system and the impact of government form on them.